Meeting the Moment: Bioethics in a Revolution - Wightman, Aaron (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
The United States of America is undergoing a political revolution and an underlying moral revolution. The role of bioethics during a revolution is unclear. This paper offers four suggestions for bioethics and bioethicists to meet our current moment: abandoning partisanship and absolutism, critically considering honour, embracing outsider status, and doing things.